Mobilities of the highly skilled towards Switzerland : the role of intermediaries in defining “wanted immigrants” (2019)
These are the kind of stories that you hear when you start asking highly educated foreigners in Switzerland about their lives. You encounter all kinds of situations: from the unemployed trailing spouse to the successful entrepreneur; from the former student struggling to renew his residence permit to the hyper-mobile businessman; from the stateless man trying to live with the person he loves to the cross-border worker; from the undeclared woman living with friends to the newly naturalised Swiss citizen. These stories demonstrate the porosity of borders in our world: some people cross them so often that they do not notice them anymore, while others have difficulty moving from one Swiss canton to another. These stories show the importance of individual situations – a single encounter, discovery, or decision can play a crucial role in the migration process. These stories illustrate the complex relationship between individuals’ goals and the social contexts in which they are embedded, which may be more or less supportive or beneficial.